2000
DOI: 10.1021/om000790l
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Intramolecular Permutation (Pseudorotation) at the Central Antimony Atom and Strong Equatophilicity of an Iron and a Ruthenium Ligand in Pentacoordinate Hypervalent Antimony Compounds

Abstract: Diastereomeric pentacoordinate hypervalent stiboranes with an Sb−Fe bond {4a and 4b:  RfRfm*Sb*FeCp(CO)2 {Rf = o-C6H4C(CF3)2O-, Rfm* = o-C6H4C*(CF3)(Me)O-} were synthesized by the reaction of stiboranide anion, RfRfm*Sb*-Li+ (3-Li), with CpFeI(CO)2 in the presence of AgBF4. The carbonyl group of 4 was replaced with triphenylphosphine by irradiation with a tungten lamp to give a mixture of four diastereomers {5a−5d:  RfRfm*Sb*Fe*Cp(CO)(PPh3)}. Each of the diastereomers was separated by TLC, and the relative ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In search of such ligands, we were drawn by the fact that antimony species such as Ph 4 SbX (X = halogen) become increasingly ionic as the size of the halogen increases . This behavior, which is promoted by the electropositive character of antimony, suggested to us that a tetraorganostiboranyl (R 4 Sb) ligand may possess strong σ-donating properties and may be well-adapted for the formation of T-shaped 14-electron transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In search of such ligands, we were drawn by the fact that antimony species such as Ph 4 SbX (X = halogen) become increasingly ionic as the size of the halogen increases . This behavior, which is promoted by the electropositive character of antimony, suggested to us that a tetraorganostiboranyl (R 4 Sb) ligand may possess strong σ-donating properties and may be well-adapted for the formation of T-shaped 14-electron transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…At 110 °C (383 K), the pseudorotational barriers were 31.3 ( 11a to 11b ) and 31.7 kcal/mol ( 11b to 11a ), which were slightly higher than those of RfRfm*Sb*FeCp(CO) 2 (30.5 ( 15a to 15b ) and 30.2 kcal/mol ( 15b to 15a )) and RfRfm*Sb*RuCp(CO) 2 (30.7 ( 16a to 16b ) and 30.4 kcal/mol ( 16b to 16a )) 1 and much higher than that of Rf 2 Sb*Cl ( 13 ; 14.6 kcal/mol) 10 and those of RfRfm*Sb*( p -CH 3 C 6 H 4 ) (28.1 kcal/mol ( 14a to 14b ), 27.7 kcal/mol ( 14b to 14a )) 12 (Table ). Therefore, the strong “equatophilicity”, which was observed in the iron and ruthenium compounds, was comfirmed in these cases, too. Although the energy difference between the group 6 (Mo) and the group 8 transition metals (Fe and Ru) was small, we might explain the difference on the basis of the electronic effect.…”
Section: Resultsmentioning
confidence: 66%
“…In the preceding paper we reported the synthesis and isomerization of diastereomeric RfRfm*Sb*FeCp(CO) 2 ( 15 ) and RfRfm*Sb*Fe*Cp(CO)(PPh 3 ) ( 15-PPh 3 ) and confirmed that isomerization of these complexes took place through a Berry pseudorotation process at the Sb atom. The energy barriers of the pseudorotation at the Sb atom in these compounds were determined to be high (30−33 kcal/mol); thus, the apicophilicity of the transition metal (group 8 element) fragments should be considered to be less than that of the p -tolyl group.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This is well explained by the increased equatophilicity for the iron fragment resulting from the strong electron-donating power. The large barriers for RfRfm*SbMoCp(CO) 3 and RfRfm*SbMCp(CO) 2 (M = Fe, Ru) [12,13] are also explained by the high equatophilicity. There is, however, a discrepancy between the order of the energy barrier and the donor power implied from the Mössbauer spectra.…”
Section: Relation Between Donor Power and Molecular Structurementioning
confidence: 93%